Overtaking collision avoidance for small autonomous uncrewed aircraft using geometric keep-out zones - Hawes, Nathaniel C.; Wilhelm, Jay P. (Frontiers in Aerospace Engineering, 2023)
Autonomous uncrewed aircraft will require collision avoidance systems designed with autonomy in mind as they integrate into the increasingly crowded national airspace system. Current uncrewed aircraft collision avoidance systems typically require a remote pilot to execute avoidance or provide poorly defined guidance that does not benefit autonomous systems. Path Recovery Automated Collision Avoidance System re-plans flight paths to adjust to collisions autonomously using path planners and keep out zones but does not currently detect or mitigate overtaking collisions. This work investigates the effect of geometric keep out zones on the overtaking scenario for autonomous uncrewed aircraft. Keep out zone shapes were developed by relating relative velocities and turn rates of the aircraft in the overtaking scenario and tested using the Path Recovery Automated Collision Avoidance System. Operational ranges for approach heading, relative velocity, and look-ahead time were then determined. The developed set of keep out zones prevented intruder aircraft from entering the minimum separation distance of one wingspan of the mission aircraft in the overtaking scenario for scenarios with look-ahead times between 5 and 12 seconds, relative velocities of 2 to 20, and approach angles between 110 • and -110 • measured from the heading of the main UAS. Minimum separation was maintained for low-speed encounters with relative velocities between 1.1 and 2.0 for look-ahead times between 2 and 8 seconds for all approach angles. With look-ahead times ranging from 5 to 8 seconds, overtaking collisions of all tested approach angles and relative speeds are handled with more than twice the separation required for success, showing that the developed keep out zones are feasible for implementation on possible autonomous collision avoidance systems.